PENGARUH PERTUMBUHAN NILAI TABUNGAN PERTUMBUHAN NILAI DEPOSITO DAN PERTUMBUHAN NILAI KREDIT TERHADAP KINERJA OPERASIONAL PADA LEMBAGA PERKREDITAN DESA (LPD) DI KABUPATEN BADUNG - I Wayan Suardiyasa; I Wayan Sukadana; I Wayan Widnyana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2021)
The ability of the LPD to generate maximum profit / profit, cannot be separated from third party funds in the form of savings and deposits as well as productive assets in the form of credit owned by the LPD to carry out operational activities so that later it can generate added value for the LPD, namely profit / profit with the funds it has. what is called rentability, one of the components to measure rentability is the BOPO ratio, which is the ratio between operating costs and operating income. The purpose of this study was to determine the effect of growth in the value of savings, deposits, and credit on operational performance (BOPO ratio) in LPDs in Badung Regency. The population in this study were all LPDs in Badung Regency in the 2017-2019 period. The sampling method used in this study was the Proposional Stratified Sampling method with a sample of 55 LPDs. The data analysis techniques used in this study were descriptive statistics, classical assumption tests, and data analysis. The data analysis method used is multiple linear regression analysis. The results showed that the growth in savings value has a positive and significant effect on operational performance (BOPO ratio), deposit value growth has a positive and insignificant effect on operational performance (BOPO ratio), and credit value growth has a negative and significant effect on operational performance (BOPO ratio). All independent variables consisting of growth in the value of savings, deposits, and credit have an effect of 4.6% on operational performance (BOPO ratio), while the remaining 95.4% is influenced by other factors not explained in this research model.